Ultrahigh Catalytic Activity of l‐Proline‐Functionalized Rh Nanoparticles for Methanolysis of Ammonia Borane. Issue 2 (28th November 2018) - Luo, Wenxiu; Cheng, Wei; Hu, Min; Wang, Qi; Cheng, Xia; Zhang, Yun; Wang, Yi; Gao, Daojiang; Bi, Jian; Fan, Guangyin
Abstract: The synthesis of ultrafine and well‐distributed rhodium nanoparticles (NPs) with high efficiency toward methanolysis of ammonia borane (AB) is crucially important but challenging. A facile approach has been developed for synthesizing ultrafine and uniform Rh NPs deposited on carbon by using the small soluble organic molecule (SOM) ofl ‐proline (PRO) as capping agent (Rh‐PRO/C). The enrichment of N, O‐coordination sites for the metal precursor by using PRO was found to be the key to the synthesis Rh‐PRO/C. The as‐prepared Rh‐PRO/C showed high catalytic activity for ammonia borane methanolysis with the highest total turnover frequency (TOF) of 1035 mol H 2 (molRh min) −1 under basic conditions, which was three times higher than that of the state‐of‐the‐art Rh‐based catalysts. The excellent catalytic performance of Rh‐PRO/C was ascribed to the well‐dispersed Rh NPs and the PRO‐functionalized metal surface, which can provide more active sites for the reaction. The merit of size‐controlled synthesis combined with metal NP surface modification by SOMs is likely to be beneficial in various catalytic fields. Abstract : Go PRO :l ‐Proline with intrinsically enriched N, O‐coordination sites was employed as a size controller and bound ligand for the synthesis of ultrasmall and uniform functionalized Rh nanoparticles (NPs). The ultrafine functionalized Rh NPs were supported on carbon and showed high catalytic activity for the methanolysis of ammonia borane with a turnover frequency of 1035 molH2 (molRh min) −1 under basic conditions.